Interactive Effect of Tillage and Phosphate Fertilization in Conjunction with FYM to Sorghum+Greengram Intercropping System on Physico-chemical Properties of the Soil - Laddha, K C; Totawat, K L (Annals of Arid Zone, 2016)
Tillage operations, particularly disc and chisel ploughing, on medium textured soils for two consecutive years (kharif. 1989 and J 990) significantly lowered the bulk density and increased soil porosity, water hOld~g capacity, hydraulic conductivity and basic infiltration rate of the soil. Incorpot-ation of farm yard manure and phosphate fertilization improved the physical conditions of the soil and the stored soil moisture profile.